2011
DOI: 10.1038/clpt.2011.104
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Obesity for Drug Therapy: Limitations and Challenges

Abstract: Obesity has become a worldwide challenge with significant health and socioeconomic implications. One of the major implications is its impact on drug therapy. In order to gain a better understanding of this impact, we surveyed the regulatory guidances, the newly approved molecular entity drug products, and drug product labels in the Physician's Desk Reference. This review summarizes the findings of the survey along with the existing knowledge on pharmacokinetic and pharmacodynamic changes associated with obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
181
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(194 citation statements)
references
References 70 publications
3
181
0
7
Order By: Relevance
“…Indeed, the pathophysiological changes associated with both obesity and critical illness may have additive effects on altered pharmacokinetics (PK), although there are very limited published data on this topic (11,12). The physiological differences in obese patients include changes in regional blood flow, increased cardiac output, and increased fat and lean mass (13). These changes may alter PK and PK/pharmacodynamics (PK/PD) of antimicrobials, necessitating dosing adjustment.…”
mentioning
confidence: 99%
“…Indeed, the pathophysiological changes associated with both obesity and critical illness may have additive effects on altered pharmacokinetics (PK), although there are very limited published data on this topic (11,12). The physiological differences in obese patients include changes in regional blood flow, increased cardiac output, and increased fat and lean mass (13). These changes may alter PK and PK/pharmacodynamics (PK/PD) of antimicrobials, necessitating dosing adjustment.…”
mentioning
confidence: 99%
“…This could be attributed to alterations in the distribution, metabolism and/or transport of the drug. Indeed, increased cytochrome P450 2E1 (CYP2E1) activity leading to the increased clearance of chlorzoxazone has been reported in obese patients (9) . Studies in genetic rodent models of obesity have reported altered expression of hepatic drug transporters and metabolic enzymes (10 -13) .…”
mentioning
confidence: 99%
“…Various physiological and pharmacokinetic parameters are altered in the obese patient, which may impact the efficacy and toxicity of antimicrobial agents. Delays in gastric emptying have been reported to occur in the obese that may affect drug absorption, although most evidence suggests this effect is not sizeable [15]. The volume of distribution (V d ), which represents the degree to which a drug distributes in plasma volume and tissues, may be increased versus lean comparators, thus resulting in lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which a medication is protein-bound also affects V d , and obesity has been shown to alter lipoproteins and alpha1-acid glycoprotein [2]. Physiologic changes in the liver, including fatty infiltration and altered cytochrome P450 activity, may also impact drug metabolism [15]. Similarly, baseline renal clearance is generally increased in obesity because of concomitant increases in cardiac output and blood volume that result in elevated glomerular filtration rate, although the presence of commonly associated conditions such as hypertension may reverse this phenomenon by causing chronic renal disease [2,26].…”
Section: Discussionmentioning
confidence: 99%